Etika Menuntut Ilmu dalam Perspektif Hadis Talabul ‘Ilmi Faridah ‘Ala Kulli Muslim - Ilham Muhammad Abussalam; Badrudin Badrudin; Zulkifli Reza Fahmi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Hadith of the Prophet Muhammad SAW constitutes a fundamental source of Islamic teachings that plays a crucial role in shaping value systems, particularly in the field of education. One of the most essential hadiths in Islamic educational discourse is Ṭalabul ‘Ilmi Farīḍah ‘Alā Kulli Muslim, which emphasizes the obligation of seeking knowledge for every Muslim. This article aims to comprehensively examine the ethics of seeking knowledge from the perspective of this hadith and its relevance to academic life among university students. This study employs a library research method by analyzing hadith compilations, classical and contemporary hadith commentaries, and scholarly literature in Islamic education. The findings indicate that the hadith Ṭalabul ‘Ilmi Farīḍah ‘Alā Kulli Muslim not only establishes the obligation of acquiring knowledge but also embodies fundamental principles of academic ethics, including sincerity, perseverance, honesty, respect for educators, and responsibility in applying knowledge. These ethical values remain highly relevant in fostering an academic culture of integrity within higher education institutions.